ANALISIS INDEKS BAHAYA EROSI DAN ARAHAN PENGGUNAAN LAHAN PADA DAS MAREK DS BAGIAN HULU KABUPATEN BONE - Muhammad Zainal Arifin; Annas Boceng; Saida Saida (Percetakan Umi Toaha Makassar, 2022)
This study aims to analyze the amount of erosion that occurs and the erosion that can be tolerated in the upstream Marek DS watershed, analyze the erosion hazard index in the upstream Marek DS watershed, and analyze land use in accordance with conservation patterns that can be applied to land due to erosion. This research was conducted using the Universal Soil Loss Equation (USLE) method to determine the level of erosion (A) that occurred at the research site. Make changes to the C and P values to find the right direction for land use. The results show that the average erosion rate that occurs in the upstream Marek DS watershed is the largest on open land, which is 1107,965 tons/ha/year, and the tolerable erosion is 17,832 tons/ha/year on dry land mixed with shrubs. It amounted to 652.297 tons/ha/year and the tolerable erosion was 20,592 tons/ha/year. The erosion in shrubs was 613.999 tons/ha/year and the tolerable erosion was 17.456 tons/ha/year. The tolerable erosion rate in secondary dryland forest was 11,372 tons/ha/year and the rate of erosion was 17,103 tons/ha/year. The smallest erosion on rice fields was 0.125 tons/ha/year and the tolerable erosion was 29,275 tons/ha/year. The average erosion hazard index in the upstream Marek DS watershed has a low value of 0.280% or 10,822 ha, namely in paddy fields; a moderate value of 5.671% or 219.079 ha, namely in secondary dryland forest, and a very high value, respectively, on dry land. Dry land agriculture mixed with shrubs accounts for 48.102% (or 1858.305 ha), open land accounts for 0.779% (or 30.083 ha), and dry land agriculture mixed with bushes accounts for 45.168% (or 1744.942 ha).Recommendations for land use directions in the upstream Marek DS watershed in the form of natural forest with lots of litter in secondary dryland forest and shrubs, then recommendations for medium density mixed gardens and making bench terraces on open land, and finally recommendations for high-density mixed gardens and making bench terraces for agriculture. If natural forest is mixed with shrubs and shrubs, then the recommendation for natural forest is less litter on open land.